Diapycnal and along isopycnal mixing, estimated from the tracer release experiment, at the North Atlantic oxygen minimum zone - Banyte, Donata (2012)
A deliberate Guinea Upwelling Tracer Release Experiment (GUTRE) in 2008 - 2010 was used to study diapycnal mixing and lateral stirring in the thermocline of tropical northeastern Atlantic. The ultimate goal of this work was to investigate oxygen supply pathways at the upper boundary of North Atlantic oxygen minimum zone. The mean diapycnal mixing coefficients were computed for a tracer patch integrated over 30 months. The strong variation of stratification in the tracer occupied area offered the advantage of using the advection-diffusion equation in isopycnal coordinates with the thickness-weighted averaging, when analyzing the diapycnal tracer spread. Overall, the vertical mixing estimates were found about 30% smaller than estimates in North Atlantic Tracer Release Experiment (NATRE), performed about 15° to the north from our experiment. In general, the internal wave-wave interaction models predict reduced mixing from the breaking of internal waves at low latitudes. Thus, GUTRE results are larger than parametrized by the low latitude of the site (4°N - 12°N). The mean isopycnal mixing coefficient was estimated by computing the growth of the second moment of a cloud of tracer. The zonal component of lateral mixing was found more than two times larger than the meridional component. The finding reflects the stretching effect of zonal jets prevalent in the tropical Atlantic Ocean. The application of conceptual jet model allowed to evaluate the mean zonal jet velocities which cause an enhancement of mixing in zonal direction. Additionally, the effective mixing coefficient was computed which indicated that zonal jets do not merely stretch the tracer patch in zonal directions, but increase mixing by increasing tracer gradients. The uncertainties of the estimates were inferred from synthetic particle release using a high resolution ocean circulation model. Finally, a large database of vertical oxygen profiles in oxygen minimum region and high precision diapycnal mixing estimates allowed for a good estimate of diapycnal ...